Comparison of Glyburide and Insulin In Women with Gestational Diabetes Mellitus and Associated Perinatal Outcome: a Randomized Clinical Trial - Masoomeh Mirzamoradi (Acta Medica Iranica, 2015)
Insulin is currently the drug of choice in treating patients with gestational diabetes mellitus but insulin is expensive, inconvenient to store and use and probably associated with more risks of asymptomatic hypoglycemia in comparison with some oral agents. This randomized clinical trial was conducted to evaluate the efficacy and safety of glyburide in patients with gestational diabetes mellitus in comparison with insulin therapy. Pregnant women aged between 18-45 years with singleton pregnancies and in their 24-36 weeks of gestation were assessed for eligibility. Women with gestational diabetes mellitus were randomly allocated to two insulin and glyburide groups and compared with maternal and neonatal outcome. Ninety-six women with gestational diabetes mellitus enrolled in the study. At screen and treated fasting and post-prandial blood glucose levels were similar in both groups. Time for beginning the treatment to control the glycemic index was 28.30 (±20.60) days in the insulin group and 22.56 (±18.86) in the glyburide group. There was no statistically significant difference in time-to-control the blood glucose level in two studied group. Time, between beginning the treatment of GDM and delivery, was 53.22 (±28.96) days in the insulin group and 56.67 (±30.47) in the glyburide group. There was no statistically significant difference between the times of treatment-to-delivery in two studied groups. There were no statistically significant differences between maternal and neonatal outcomes in two studied groups. Glyburide can effectively and safely control the glycemic index in women with gestational diabetes mellitus in comparison with insulin.